The inquiry method in teaching the new social studies to the educable mentally retarded - Longanilla, Tessie T. 1949-; Sison, Waldetrudes Montojo (1973)
The aim of the study was to show the applicability of teaching the new social studies using the inquiry method to the educable mentally retarded. The research shows that the teaching of the new social studies using the inquiry method to the retarded children provides opportunities for the acquisition of intellectual, social and occupational skills compulsory to their security and independence.
"May, 1973."
Vita.
Thesis (Master of Arts in Teaching - Special Education : Mental Retardation)--University of the Philippines, Diliman.
Keywords: Social sciences -- Study and teaching (Elementary) -- Philippines; Children with mental disabilities -- Philippines